Time of Emergence of Surface Ocean Carbon Dioxide Trends in the North American Coastal Margins in Support of Ocean Acidification Observing System Design - Turk, Daniela; Wang, Hongjie; Hu, Xinping; Gledhill, Dwight K.; Wang, Zhaohui Aleck; Jiang, Liqing; Cai, Wei-Jun (Frontiers in Marine Science, 2019)
Time of Emergence (ToE) is the time when a signal emerges from the noise of natural variability. Commonly used in climate science for the detection of anthropogenic forcing, this concept has recently been applied to geochemical variables to assess the emerging times of anthropogenic ocean acidification (OA) mostly in the open ocean using global climate and Earth System Models. Yet studies of OA variables are scarce within costal margins, due to limited multidecadal time-series observations of carbon parameters. ToE provides important information for decision making regarding strategic configuration of observing assets to ensure they are optimally positioned either for signal detection and/or process elicitation and to identify the most suitable variables in discerning OA-related changes. Herein, we present a short overview of ToE estimates on an OA variable, CO2 fugacity ƒ(CO2,sw), in the North American ocean margins using coastal data from Surface Ocean CO2 Atlas (SOCAT) V5. ToE suggests an average theoretical timeframe for an OA signal to emerge of 23(±13) years, but with considerable spatial variability. Most coastal areas are experiencing additional secular and/or multi-decadal forcing(s) that modifies the OA signal, and such forcing may not be sufficiently resolved by current observations. We provide recommendations that will help scientists and decision makers design and implement OA monitoring systems in the next decade addressing the objectives of OceanObs19 in support of the United Nations Decade of Ocean Science for Sustainable Development (2021-2030) and the Sustainable Development Goal (SDG) 14.3 Target to “Minimize and address the impacts of OA ”.